MONETARY DETERMINANTS OF HOUSE PRICES IN CENTRAL AND EASTERN EUROPEAN COUNTRIES - Shevchuk Viktor (PRACE NAUKOWE UNIWERSYTETU EKONOMICZNEGO WE WROCŁAWIU, 2022)
This research aimed at the empirical estimation of the monetary determinants of house prices in the Czech Republic, Hungary, Poland, and Romania. The application of quarterly panel data for the period 2010-2019 indicates that a central bank policy rate increase was responsible for the fall in house prices, with a similar effect on house prices by a higher consumer inflation and nominal (real) exchange rate undervaluation. There was no reaction of house prices to the business cycle. However, the housing boom had a positive contribution to cyclical changes in output, while not affecting consumer prices and exchange rate.
Keywords: house prices; interest rate; exchange rate; Central and Eastern Europe